Influence of incorporating sesame residue flour on bread quality (Research, Society and Development, 2020)
Sesame residue flour can be used for food production, due to its nutritional properties, being considered an alternative to improve the nutritional quality of food products. The aim of this study was to evaluate the influence of the incorporation of sesame residue flour on the physical, physical-chemical characteristics and texture profile of the breads. The sesame residue flour (FRG) was obtained from the residue (cake) generated during the sesame oil extraction process. For the preparation of the breads four formulations were used: the standard formulation (control), produced only with wheat flour, and the formulations with wheat flour and FRG incorporated in the proportions of 5, 10 and 15%. The experimental data of the physical and physical-chemical characterization of the breads regarding the parameters: water content, color, water activity, titratable acidity, lipids and pH, were subjected to analysis of variance and the treatment means compared by the Tukey test, at the level of 5% probability, using the ASSISTAT program. The texture parameters determined were: firmness, cohesiveness, elasticity, chewability and resistance, for each formulation six samples were used, obtaining the final average. The partial replacement of wheat flour with sesame residue flour in the bread formulations, resulted in changes in the characteristics evaluated, however, they remained in the desirable consumption patterns, and can be considered a viable alternative for the enrichment of food.